2011
DOI: 10.1007/s10623-011-9520-2
|View full text |Cite
|
Sign up to set email alerts
|

Steiner triple systems satisfying the 4-vertex condition

Abstract: Higman asked which block graphs of Steiner triple systems of order v satisfy the 4-vertex condition and left the cases v = 9, 13, 25 unsettled. We give a complete answer to this question by showing that the affine plane of order 3 and the binary projective spaces are the only such systems. The major part of the proof is to show that no block graph of a Steiner triple system of order 25 satisfies the 4-vertex condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While the cases m = 9 and m = 13 can be easily settled, the case m = 25 remained open for four decades. Following the advice of M. Klin, P. Kaski et al obtained the negative answer (see [26]), essentially relying on the use of computer and some extra clever ad hoc tricks (the complete enumeration of all ST S(25) looks hopeless at the moment).…”
Section: The 4-vertex Conditionmentioning
confidence: 99%
“…While the cases m = 9 and m = 13 can be easily settled, the case m = 25 remained open for four decades. Following the advice of M. Klin, P. Kaski et al obtained the negative answer (see [26]), essentially relying on the use of computer and some extra clever ad hoc tricks (the complete enumeration of all ST S(25) looks hopeless at the moment).…”
Section: The 4-vertex Conditionmentioning
confidence: 99%
“…He found that either the system is a projective space PG(m, 2) or v is one of 9, 13, 25. In [25] the cases 13 and 25 are ruled out, so that the only other example is the affine plane AG (2,3). The examples are rank 3.…”
Section: Block Graphs Of Steiner Triple Systemsmentioning
confidence: 99%
“…As non-rank 3 srgs with the t-vertex condition for t > 3 appear to be very rare, there has been an ongoing research effort to discover new examples and to understand their nature (cf. [18,19,23,24,29,31]).…”
Section: Introductionmentioning
confidence: 99%